PTU-101 Outcomes of transplantation for hepatopulmonary syndrome are improving. (17th June 2017) - Kathawala, M; Roberts, K; Isaac, J; Ferguson, JW
Abstract : Introduction: Hepatopulmonary syndrome (HPS) is characterised by intrapulmonary vascular vasodilatation leading to hypoxaemia, occurring in the setting of portal hypertension. Liver transplantation (LT) is the only known effective therapy for HPS. In this study, we aim to (1) evaluate whether outcomes have improved over time (2) examine whether severe HPS is a barrier to transplantation. Method: Clinical outcomes were evaluated in patients with HPS undergoing liver transplantation (1999 to 2016) using a prospectively accrued database. Patients were stratified according to era of transplantation; 1999–2007 and 2008–2016. Furthermore we evaluated outcomes for patients with severe HPS as defined as PaO2 of ≤50 mm Hg (or 6.7 kPa). Results: Over 18 years, 31 patients underwent liver transplantation for HPS (58% female, median age at time of transplant: 52 years, cumulative follow-up from transplantation till end of study: 179 patient-years). The median time from listing to LT was 107 days amongst patients transplanted during the earlier era, whereas it was longer at 214 days for those transplanted during the later era. The median length of intensive care and hospital stay was 7 days and 16 days respectively overall. This did not change during the two eras, as did not the time to cessation of oxygen therapy (median of 47 days). 30 day and one-year mortality post LT was 9.7% (3/31) and 22.6% (7/31) respectively. Improved survival outcomes were demonstrated in the later era (one-year mortality during 1999–2007 was 36.4%, and 15% during 2008–2016). One-year mortality also improved in the later era (60% to 0%)%) for patients with non-severe HPS. 14 patients (45.2%) had severe HPS, with a one-year mortality of 28.6% (4/14) post LT. This includes one-year mortality during 1999–2007 of 25% (1/4) and during 2008–2016 of 30% (3/10). In the severe HPS group the median baseline PaO2 had fallen from 6.9 to 6.1 kPa respectively over the interval eras. Conclusion: Our study has demonstrated improved overall survival outcomes post-LT for HPS over two successive eras. Patients with severe hepatopulmonary syndrome should be considered for transplantation. Disclosure of Interest: None Declared